Evaluation of distress among cancer patients in Bengaluru City: A cross-sectional study - Anuradha Sadanand Bandiwadekar; Namita Shanbhag; Manjunath P Puranik (Wolters Kluwer Medknow Publications, 2020)
Background: Distress is common among people affected by cancer. Distress can influence the quality of life and participation in medical treatment. Although not everyone wants to openly discuss their feelings and emotional distress, research shows that early advice, support, education, and intervention can avoid the demand for intensive intervention. Aims: This study aimed to evaluate the extent and source of distress among cancer patients using the National Comprehensive Cancer Networks Distress Thermometer (DT). Materials and Methods: A cross-sectional descriptive study was carried out at a tertiary care hospital, Bengaluru. A study was conducted among 384 cancer patients attending a tertiary care hospital, Bengaluru, from June to August 2012, after obtaining the consent. The DT consisted of a 48-item questionnaire representing the problems commonly experienced by cancer patients. The patients were asked to mark any sources of distress. Mann-Whitney U-test, Kruskal-Wallis, and Spearman's rho were employed using SPSS software 16.0 version. Results: Out of 384 cancer patients, 88 (22.92%) had a distress score of 7. Age and socioeconomic status were significantly associated with distress, whereas gender was not. Practical problems, family problems, emotional problems, religious concerns, and physical problems were significantly associated with the distress. Statistically significant difference was noted between patients with head-and-neck cancer against other cancers with regard to practical problems, religious concerns, and physical problems. Conclusion: This study documents a significant level of distress among cancer patients. Hence, there is a need to develop appropriate coping strategies in cancer patients.